2015
DOI: 10.1021/acsami.5b06341
|View full text |Cite
|
Sign up to set email alerts
|

Electron-Beam-Induced Deposition as a Technique for Analysis of Precursor Molecule Diffusion Barriers and Prefactors

Abstract: Electron beam induced deposition (EBID) is a directwrite chemical vapor deposition technique in which an electron beam is used for precursor dissociation. Here we show that Arrhenius analysis of the deposition rates of nanostructures grown by EBID can be used to deduce the diffusion energies and the corresponding pre-exponential factors of EBID precursor molecules. We explain the limitations of this approach, define growth conditions needed to minimize errors, and explain why the errors increase systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…1D model predictions preempted the integration of a 3D beam heating simulation to our 3D FEBID solver . The effect of electron-beam heating during FEBID has been previously recognized for various materials, , and the 3D simulations reported here including the heating effect are consistent with previous observations. Simulations with the enhanced capability revealed the important role that heat transfer plays in dictating the final deposit geometry: a thermal gradient develops in the deposit that induces an opposing precursor concentration gradient.…”
supporting
confidence: 86%
See 2 more Smart Citations
“…1D model predictions preempted the integration of a 3D beam heating simulation to our 3D FEBID solver . The effect of electron-beam heating during FEBID has been previously recognized for various materials, , and the 3D simulations reported here including the heating effect are consistent with previous observations. Simulations with the enhanced capability revealed the important role that heat transfer plays in dictating the final deposit geometry: a thermal gradient develops in the deposit that induces an opposing precursor concentration gradient.…”
supporting
confidence: 86%
“…An updated value of E a = 0.62 eV (dashed line) produced simulation results that predicted 3D FEBID experiments and is taken as an estimate of the E a for the MeCpPt IV Me 3 –PtC x interface. Surface diffusion D ( T ) is less sensitive to temperature changes (solid blue line) based on data provided in ref with D o = 42 μm 2 /s and E a( D ) = 122 meV, at least when compared to τ­( T ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work by Cullen and collaborators [20,24] has shown how both the activation energies and pre-exponential factors for desorption and diffusion can be deduced from FEBID experiments under stationary beam conditions if certain prerequisites are fulfilled. This approach may also be applied to the CoFe-and Nb-precursor to deduce the temperature dependence of D. This will then allow to take properly into account how beam-induced heating might change the growth rates for 3D growth using the CoFe-and Nb-precursor due to increased desorption and faster diffusion, as was previously investigated for the Pt-precursor [25].…”
Section: Discussionmentioning
confidence: 99%
“…The equilibrium precursor surface coverage (θ ο ) for the flat PtC 5 surface for our gas injection system was calculated to be 0.73 when the precursor nozzle was oriented at 38°with respect to the substrate normal vector and the precursor capillary tube. Parameters necessary for this calculation were (1) the precursor sticking probability (unknown, assumed δ = 1), (2) the surface diffusion coefficient 0.4 μm 2 /s of MeCpPt IV Me 3 31 and (3) the mean surface residence time (τ) of 100 μs for the MeCpPt IV Me 3 molecule adsorbed on PtC 5 . 26 Regarding the parameter (τ), an experimentally derived value of ∼29 μs is reported in the literature, 32 yet we have found that by increasing the parameter to 100 μs a better fit to our experiments is achieved.…”
Section: Simulation Parametersmentioning
confidence: 99%